A coding variant in FTO confers susceptibility to thiopurine-induced leukopenia in East Asian patients with IBD. Issue 11 (24th August 2016) - Kim, Han Sang; Cheon, Jae Hee; Jung, Eun Suk; Park, Joonhee; Aum, Sowon; Park, Soo Jung; Eun, Sungho; Lee, Jinu; Rüther, Ulrich; Yeo, Giles S H; Ma, Marcella; Park, Kyong Soo; et al.
Abstract : Objective: Myelosuppression is a life-threatening complication of thiopurine therapy, and the incidence of thiopurine-induced myelosuppression is higher in East Asians than in Europeans. We investigated genetic factors associated with thiopurine-induced leukopenia in patients with IBD. Design: A genome-wide association study (GWAS) was conducted in thiopurine-treated patients with IBD, followed by high-throughput sequencing of genes identified as significant in the GWAS or those involved in thiopurine metabolism (n=331). Significant loci associated with thiopurine-induced leukopenia were validated in two additional replication cohorts (n=437 and n=330). Functional consequences of FTO (fat mass and obesity-associated) variant were examined both in vitro and in vivo. Results: The GWAS identified two loci associated with thiopurine-induced leukopenia (rs16957920, FTO intron; rs2834826, RUNX1 intergenic). High-throughput targeted sequencing indicated that an FTO coding variant (rs79206939, p.A134T) linked to rs16957920 is associated with thiopurine-induced leukopenia. This result was further validated in two replication cohorts (combined p=1.3×10 −8, OR=4.3). The frequency of FTO p.A134T is 5.1% in Koreans but less than 0.1% in Western populations. The p.A134T variation reduced FTO activity by 65% in the nucleotide demethylase assay. In vivo experiments revealed that Fto −/− and Fto +/− mice were more susceptible to thiopurine-induced myelosuppression than wild-type mice. Conclusions: The results suggest that the hypomorphic FTO p.A134T variant is associated with thiopurine-induced leukopenia. These results shed light on the novel physiological role of FTO and provide a potential pharmacogenetic biomarker for thiopurine therapy.